السياحة المظلمة: مقاربة مفاهيمية - قاسي, نجاة (Revue jurisprudence, 2019)
During the past century, there has been an increase of academic interest in one of the tourism’s forms related to death, suffering, violence and pain, which has emerged in recent years as a result of spill over due to globalization, the attraction of tourists to such events and sites, and other factors that made the battlefields, Massacres, disasters a popular tourism destination. Which allowed the establishment of the so-called "dark tourism", through making these sites into museums or dark tourism attractions, those latters allows the tourist to open a window over a past connected to suffering that occurred in these sites and events and enable him to live different experiences. Hence, the purpose of this research is to pursue the literature and compile a comprehensive list of definitions and potential visitor motivations to sites of dark tourism.